MODEL PENGEMBANGAN KURIKULUM PAI SMP DI KOTA SEMARANG - Makhshun, Toha (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2018)
A research based article â€œThe model of PAI curriculum development at Junior high school in Semarangâ€ is intended to see how far the development of PAI curriculum at Junior High School in Semarang. The main problem in this research is:Â Â  how is the development of PAI curriculum at Junior high school in Semarang.Â The techniques of collecting data applied in this research are (1) observation to collect data of PAI curriculum development application at NASIMA Junior High School and Sultan Agung Islamic Junior High SchoolÂ  I; (2) An interview to getÂ  a clear, comprehensive and indepth information about PAI curriculum policy and itâ€™s implementation at Nasima and Sultan Agung Islamic Junior High School I; (3) documentation, is for collectingÂ  a history documentation, to formulate a curriculum. Descriptive-interpretative is used to analyze collected data.The reseach result shows that Nasima Junior High School and Sultan Agung Junior High School â€“ Semarang have innovative and strategic steps in developing a curriculum. The curriculum is interpretated based on the needs of school and society through a religion and Islamic school cultureÂ Â  activity.